Improvement of magnetic and dielectric properties of magnetoelectric BST-NCZMF nano-composite. (3rd May 2020) - Henaish, A. M. A.; Mostafa, M.; Salem, B. I.; Hemeda, O.M.
ABSTRACT: A series of composite "BST"+ "NCZMF" were prepared using high energy ball milling method. The structural characterization for synthesized samples were carried out using (XRD), (FTIR) and (HRTEM). The surface morphology of BST at different ferrite content (x%) was studied by (SEM). XRD pattern confirms that both parent phases BST and spinel NCZMF are pure phases. The sample x = 40% has the highest value of tetragonality factor which may be candidate for ME application and piezoelectric sensors. For the sample x = 40% the second stage is shifted to higher temperature which confirms that the thermal stability of the sample is increased by increasing the ferrite content for this sample. The EDX has been utilized to confirm the grains of these two phases. FTIR show the successful formation of composite samples which is also observed from XRD pattern. The hysteresis loops show low coercive field (Hc) indicating that our composite are soft magnetic material. The permeability of nanocomposite samples were measured as a function of temperature in the range from 300 to 700 K at constant frequencies 1KHZ and 10KHZ. Magnetoelectric coefficient decreases with increasing magnetic field for all composite samples at higher magnetic field the magnetoelectric coefficient get saturated producing constant ΔE / ΔH. the dielectric loss decrease by increasing frequency, this means that our composite samples can be used at higher frequency with low dielectric loss.